2016
DOI: 10.2478/teen-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

Triaxial Measurement Method for Analysis of Residual Stress after High Feed Milling by X-Ray Diffraction

Abstract: Surface integrity is a broad term which includes various quality factors affecting the functional properties of parts. Residual stress is one of these factors. Machining generates residual stresses in the surface and subsurface layers of the structural elements. X-ray diffractometry is a non-destructive method applicable for the measurement of residual stresses in surface and subsurface layers of components. The article is focused on the non-destructive progressive method of triaxial measurement of residual st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…It is well known, the high surface temperatures and gradients with high temperature can cause the change of surface integrity, such as microstructures changes, phase transformation, plastic deformation and high residual tensile stress. Bushley et al [23] observed the white layer when milling Inconel 718, phase transformation was mentioned by Liao et al [24] and residual stress when turning was analysed by Devillez et al [22]. As explained previously, the information obtained by semi-synthetic thermocouple is applicable for analyse of temperature distribution on cutting edge during the formation of a single chip (Fig.…”
Section: Results Of Experiments and Discussionmentioning
confidence: 84%
“…It is well known, the high surface temperatures and gradients with high temperature can cause the change of surface integrity, such as microstructures changes, phase transformation, plastic deformation and high residual tensile stress. Bushley et al [23] observed the white layer when milling Inconel 718, phase transformation was mentioned by Liao et al [24] and residual stress when turning was analysed by Devillez et al [22]. As explained previously, the information obtained by semi-synthetic thermocouple is applicable for analyse of temperature distribution on cutting edge during the formation of a single chip (Fig.…”
Section: Results Of Experiments and Discussionmentioning
confidence: 84%
“…The accuracy of the XRD-sin 2 ψ residual stress measurement depends on the minimization of various measurement errors derive from several sources. Materials to be measured, machine limitation, methods of analyses, manpower and software measurement conditions are the main big uncertain sources [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the work-piece is constrained within the groove by a stationary constraint die; and this die also stops the work-piece and force sit to turn at an angle by shear as in a regular ECAP process. [6,7] This set-up effectively makes the ECAP process continuous. Other ECAP parameters, such as the die angle and the strain rate, can also be easily incorporated into the facility.…”
Section: Introductionmentioning
confidence: 99%